Implementation of Religious Culture-Based PAI Learning in Shaping Early Childhood Character at PAUD Al-Ishlah Kuala Jambi - Siti Romlah; Khoirotul Muslimah (STAI Al-Mas'udiyah, 2025)
This study aims to analyze the implementation of religious culture-based Islamic Religious Education (PAI) learning in shaping early childhood character at PAUD Al-Ishlah Kuala Jambi. A qualitative case study approach was employed to explore learning practices, value internalization, and influencing factors within a natural educational setting. Data were collected through participatory observation, semi-structured interviews with teachers and school administrators, and document analysis, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that PAI learning is implemented through an integrative pattern combining structured instruction, religious habituation, and a supportive learning environment. This approach is associated with the development of children’s social and moral character, particularly in cooperation, empathy, and prosocial behavior, while emotional regulation appears to develop more gradually and requires additional support. The study also shows that the effectiveness of character formation is closely related to the consistency of value integration across daily activities rather than isolated instructional practices. These findings contribute to the understanding of religious culture-based PAI learning as an integrative and contextual approach, offering both conceptual and practical insights for developing more sustainable character education models in early childhood education.